Laser B1: teacher's book with student's eBook - Mann M. Malcolm (London, Macmillan, 2013)
A lively, motivating and interesting Bl-level book specifically designed with teenagers in mind. Laser Bl provides comprehensive coverage of the grammar, vocabulary and skills required at Bl level as well as focusing regularly on exam-type tasks. Laser Bl features: Sixteen interesting and engaging topic-based units; Lexical and grammatical syllabus based on the Bl level of the Council of Europe's Common European Framework of Reference ; Comprehensive coverage and development of core reading, writing, listening and speaking skills ; Dictionary Corner sections covering topic-based vocabulary and collocations ;Phrase Bank! sections presenting functional phrases and expressions ; Soundstation sections clarifying emphasis and stress patterns ; Use your English sections consolidating structures from the unit ; Get ready to write sections developing writing skills ; Revision sections after every two units ; Sixteen detailed and structured writing planners, including space for students' own notes ; Comprehensive databases covering patterns and collocations, speaking and grammar ; Further reading and listening practice in the Workbook ; A page-faithful Digibook version of the Student's Book ; Student's CD-ROM with unit-specific exercises to reinforce the grammar and lexical material ; Teacher's DVD-ROM with unit and term tests as well as a final test, a Test Generator and a series of teacher-related videos